Image quality comparison of abdominal MSCT: Injector vs. Syringe Method - Faesol, Ahmad; Permana, Hendry Dwi Widya; Hidayat, Fathur Rachman (Universitas 'Aisyiyah Yogyakarta, 2025)
Afriani, D. (2024). Buku Ajar Epidemiologi Penyakit Tidak Menular. Penerbit NEM. Choi, M., Lee, Y., & Jung, S. (2022). The Image Quality and Diagnostic Performance of CT with Low-Concentration Iodine Contrast (240 mg Iodine/mL) for the Abdominal Organs. Diagnostics, 12(3), 752. https://doi.org/10.3390/diagnostics12030752 Endrikat, J., Barbati, R., Scarpa, M., Jost, G., & Ned Uber, A. E. (2018). Accuracy and Repeatability of Automated Injector Versus Manual Administration of an MRI Contrast Agent-Results of a Laboratory Study. Investigative Radiology, 53(1), 1—5. https://doi.org/10.1097/rli.0000000000000403 Flynn, W., & Vickerton, P. (2025). Anatomy, Abdomen and Pelvis: Abdominal Wall. Francis, I. R., Cohan, R. H., McNulty, N. J., Platt, J. F., Korobkin, M., Gebremariam, A., & Ragupathi, K. I. (2003). Multidetector CT of the liver and hepatic neoplasms: effect of multiphasic imaging on tumor conspicuity and vascular enhancement. AJR. American Journal of Roentgenology, 180(5), 1217–1224. https://doi.org/10.2214/ajr.180.5.1801217 Irfan Irfan, & Rahmat Widodo. (2024). Tatalaksana Pemeriksaan CT Scan Abdomen Dengan Kontras Dengan Klinis CA Recti. DIAGNOSA: Jurnal Ilmu Kesehatan Dan Keperawatan, 2(1), 113–123. https://doi.org/10.59581/diagnosa-widyakarya.v2i1.2711 Koshi, R. (2025). 153The abdominal cavity. In R. Koshi & R. Koshi (Eds.), Cunningham’s Manual of Practical Anatomy Volume 2 Thorax and Abdomen (p. 0). Oxford University Press. https://doi.org/10.1093/med/9780198939016.003.0013 Li, S., Yuan, X., Yi, Z., Dai, H., Yang, L., Dai, Z., & Yan, G. (2023). Dual-phase contrast-enhanced multislice computed tomography scans play a key role in the diagnosis of abdominal wall desmoid-type fibromatoses. Technology and Health Care : Official Journal of the European Society for Engineering and Medicine, 31(S1), 45–54. https://doi.org/10.3233/THC-236005 Li, X.-M., Reng, J., Zhou, P., Cao, Y., Cheng, Z.-Z., Xiao, Y., & Xu, G.-H. (2014). Solitary fibrous tumors in abdomen and pelvis: imaging characteristics and radiologic-pathologic correlation. World Journal of Gastroenterology, 20(17), 5066–5073. https://doi.org/10.3748/wjg.v20.i17.5066 McDermott, M., Kemper, C., Barone, W., Jost, G., & Endrikat, J. (2020). Impact of CT Injector Technology and Contrast Media Viscosity on Vascular Enhancement: Evaluation in a Circulation Phantom. The British Journal of Radiology, 93(1109), 20190868. https://doi.org/10.1259/bjr.20190868 Melikian, R., Goldberg, S., Strife, B. J., & Halvorsen, R. A. (2016). Comparison of MDCT protocols in trauma patients with suspected splenic injury: superior results with protocol that includes arterial and portal venous phase imaging. Diagnostic and Interventional Radiology (Ankara, Turkey), 22(5), 395–399. https://doi.org/10.5152/dir.2016.15232 Paparo, F., Garello, I., Bacigalupo, L., Marziano, A., Galletto Pregliasco, A., Rollandi, L., Puppo, C., Mattioli, F., Puntoni, M., & Rollandi, G. A. (2014). CT of the abdomen: degree and quality of enhancement obtained with two concentrations of the same iodinated contrast medium with fixed iodine delivery rate and total iodine load. European Journal of Radiology, 83(11), 1995–2000. https://doi.org/10.1016/j.ejrad.2014.07.010 Seeram, E. (2016). Computed Tomography: Physical Principles, Clinical Applications, and Quality Control (F. Edition (ed.)). Trigui, M., Ouanes, Y., Rahoui, M., Chaker, K., Marrak, M., & Nouira, Y. (2023). Massive hydronephrosis due to obstruction by upper urinary tract urothelial carcinoma with compression of the inferior vena cava. Urology Case Reports, 50, 102539. https://doi.org/10.1016/j.eucr.2023.102539 Wijokongko, A., Pudyastuti, S., & Widiyanto, A. (2017). Pengaruh fase pemeriksaan MSCT multiphase terhadap gambaran lesi hepar. Jurnal Teknologi Kesehatan, 7(2), 101–108.